2012
DOI: 10.1186/1742-4690-9-21
|View full text |Cite
|
Sign up to set email alerts
|

The endogenous retrovirus ENS-1 provides active binding sites for transcription factors in embryonic stem cells that specify extra embryonic tissue

Abstract: BackgroundLong terminal repeats (LTR) from endogenous retroviruses (ERV) are source of binding sites for transcription factors which affect the host regulatory networks in different cell types, including pluripotent cells. The embryonic epiblast is made of pluripotent cells that are subjected to opposite transcriptional regulatory networks to give rise to distinct embryonic and extraembryonic lineages. To assess the transcriptional contribution of ERV to early developmental processes, we have characterized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 71 publications
(106 reference statements)
3
16
1
Order By: Relevance
“…In a previous report we have shown that the promoter of Ens-1 is repressed while the expression of Sox2 is induced when CES differentiate [8]. These results are in agreement with the idea that differentiation of CES in vitro may mimic the release of the repression mediated by the dimer ENS-1/HP1γ on the promoter of Sox2 before the emergence of the neural plate.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In a previous report we have shown that the promoter of Ens-1 is repressed while the expression of Sox2 is induced when CES differentiate [8]. These results are in agreement with the idea that differentiation of CES in vitro may mimic the release of the repression mediated by the dimer ENS-1/HP1γ on the promoter of Sox2 before the emergence of the neural plate.…”
Section: Resultssupporting
confidence: 90%
“…Silencing of the gene occurs later, as final differentiation is achieved [8], [9]. In the epiblast, this expression pattern is managed by the pluripotency transcription factor Nanog and by a combination of Gata and Ets transcription factors that are expressed in the epiblast, in the hypoblast and in the prospective neural plate [8].…”
Section: Introductionmentioning
confidence: 99%
“…Whether some ERV-derived enhancers serve as docking sites for this repressor system in these adult tissues warrants exploration. There is evidence that some ERV sequences function as authentic regulators, including enhancers, in certain cells, not only during development but also in adult tissues (Pi et al 2004;Bourque et al 2008;Kunarso et al 2010;Teng et al 2011;Mey et al 2012;Schmidt et al 2012). Our data indicate that these rare coopted elements represent only exceptions within a large group, most members of which are repressed through TRIM28.…”
Section: Discussionmentioning
confidence: 74%
“…Accordingly, it is noteworthy that the long terminal repeats (LTRs) of ERVs harbor binding sites for numerous transcription factors, as expected from the needs of their own replication. Furthermore, rare ERV-contained sequences have been found to function as cisacting regulatory elements during mouse, human, and chick development through their recruitment of proteins such as POU5F1 (also called OCT4), GATA4, and CTCF (Bourque et al 2008;Kunarso et al 2010;Mey et al 2012;Schmidt et al 2012). ERVs and cellular genes can additionally be coordinately controlled in ES cells Macfarlan et al 2011Macfarlan et al , 2012.…”
mentioning
confidence: 99%
“…ERV-contained sequences regulate vertebrate development (Wang et al 2007;Bourque et al 2008;Kunarso et al 2010;Mey et al 2012;Schmidt et al 2012) and contributed, for instance, to the evolutionary diversification of the placenta (Chuong et al 2013). Moreover, ERVs can serve as tissuespecific promoters or enhancers for cellular genes, and control of some ERV-cellular gene pairs is coordinated notably in ES cells (Buzdin et al 2006;Karimi et al 2011;Macfarlan et al 2011Macfarlan et al , 2012Rebollo et al 2011).…”
mentioning
confidence: 99%